Implementasi Instrumen Zoning Regulation dalam Penanganan Lahan Kritis di DTA Kaskade Mahakam - Luhur Bintang Taufan; Rahmat Aris Pratomo (Jurnal Wilayah dan Lingkungan, 2022)
The rapid growth of critical land in the Mahakam Cascade catchment area has caused environmental damage and land degradation. There was an increase in this critical land during the last ten years in this area. It was recorded that about 15.54% of the critical land area increased from 2013 to 2018. The condition of land degradation continuously occurs due to increased land use complexity, which does not match the characteristics of the land. As a result, the carrying capacity of the land is getting worst. In responding to this condition, it is necessary to have a different instrument to handle these critical lands. This study aims to formulate directions for handling critical land in the Mahakam Cascade DTA based on the direction of critical land zoning. The first stage was to determine the zoning of critical land vulnerability levels to determine critical land zoning using the weighted overlay method. The following stage was to formulate directives on land management and use with zoning regulations using the Delphi analysis method for key stakeholders. The main findings show that six zoning classifications of critical land are divided into three protected and cultivated areas. From these findings, directions are then drawn up for critical handling of land with the concept of zoning regulation covering land use functions (permitted, limited permitted, conditionally permitted, and prohibited). The zoning regulation directive adjusts to the criticality level of the land and its use function as well as conservation and rehabilitation techniques, i.e., civil engineering approach and irrigation, vegetative, infiltration and drainage wells, which have different settings in each zoning criticality level of critical land.